Volviendo a los orígenes: la influencia del derecho civil para una protección integral de la persona - Santome-Sánchez, Aldo Alesandro (2023)
The process of constitutionalization of law, more precisely of civil law, has caused a series of positive changes for the protection of fundamental rights; however, it is necessary to mention that, prior to this step, a "civilization" of constitutional law had to be carried out, that is, a progressive incorporation of some figures of private law in the Constitution in order to protect the interests of people. In that way, the present study seeks to vindicate the civil origins of the protection of the person and their interests, making a historical review from the phenomenon of codification to how the current Civil Code of 1984 protects, within the civil jurisdiction, the protection of person.